Control of Aedes aegypti with temephos in a Buenos Aires cemetery, Argentina Control de Aedes aegypti con temefós en un cementerio de Buenos Aires, Argentina Controle de Aedes aegypti com temefós em cemitério de Buenos Aires, Argentina - Darío Vezzani; Stella Maris Velázquez; Nicolás Schweigmann (Universidade de São Paulo, 2004)
The efficacy of a larvicide, temephos, for controlling Ae. aegypti was evaluated in a cemetery in Buenos Aires, Argentina. Breeding sites decreased from 18.4% in the first study period (Nov 1998 to May 1999, without temephos) to 2.2% in the second period (Nov 1999 to May 2000, two applications), and to 0.05% in the third one (Nov 2000 to May 2001, five applications). Ovitraps with eggs decreased from 17% in the first period to 5.8% in the second period, and to 2.9% in the third one. Results suggest that, in Buenos Aires, Ae. aegypti populations are highly susceptible to temephos. It is recommended to limit the use of temephos to prevent potential epidemics rather than for routine control. Se evaluó la eficacia de un larvicida, temefós, para controlar Ae. aegypti en un cementerio de Buenos Aires, Argentina. Los criaderos descendieron de 18,4% en el primer periodo de estudio (Nov 1998 a May 1999, sin temefos) a 2,2% en el segundo (Nov 1999 a May 2000, dos aplicaciones), y a 0,05% en el tercero (Nov 2000 a May 2001, cinco aplicaciones). Las ovitrampas con huevos disminuyeron de 17% en el primer periodo a 5,8% en el segundo, y a 2,9% en el tercero. Los resultados sugieren que, en Buenos Aires, las poblaciones de Ae. aegypti son altamente susceptibles al temefós. Es recomendable limitar su uso para prevenir eventuales epidemias y no para el control rutinario. Avaliou-se a eficácia de um larvicida, temefós, para controlar Ae. aegypti em um cemitério de Buenos Aires, Argentina. Os criadouros reduziram de 18,4% no primeiro período de estudo (nov de 1998 a maio de 1999, sem temefós) para 2,2% no segundo (nov de 1999 a maio de 2000, duas aplicações), e para 0,05% no terceiro (nov de 2000 a maio de 2001, cinco aplicações). As. ovitrampas com ovos diminuíram de 17% no primeiro período para 5,8% no segundo e para 2,9% no terceiro. Os resultados sugerem que, em Buenos Aires, as populações de Ae. aegypti são altamente susceptíveis ao temefós. É recomendável seu uso para prevenir eventuais epidemias e não para o controle rotineiro.